A comparison of injuries in elite boy and girl tennis players - Safran, M. R.; Hutchinson, M. R.; Moss, R.; Albrandt, J.
The purpose of the study was to determine if a gender difference exists in injury pattern incidence and prevalence in high level USTA competitors. The study compares the incidence of injury, prevalence of injury and injury patterns in 14-16 year old participants at the USTA Girls 16´s National Tennis Championships (held in San Diego, CA) and USTA Boys´ National Hardcourt Championships (held in Kalamazoo, Michigan). Injuries that required physical or medical assistance were recorded by a trainer for participants at both tournaments from 1996 tot 1998. There were 539 participants in the Girls Nationals, accounting for 2,957 athletic exposures, and 720 participants in the Boys Nationals, with 906 singles matches and 378 doubles matches accounting for 3,324 athletic exposures. There was no significant difference in the overall rate of injury (new and recurrent) between boys and girls, but boys sustained more new injuries. The data showed that girls and boys have the similar rate of lower extremity injury, but girls have a disproportionately higher percentage of lower extremity injuries. Boys have more upper extremity and central injuries. Girls sustain more injuries to the feet, leg/calf and wrist, while boys sustain more injuries to the ankle, groin, and hand.